Machine learning prediction of future amyloid beta positivity in amyloid-negative individuals - Elaheh Moradi; Mithilesh Prakash; Anette Hall; Alina Solomon; Bryan Strange; Jussi Tohka; for the Alzheimer’s Disease Neuroimaging Initiative (Alzheimer’s Research & Therapy, 2024)
Abstract Background The pathophysiology of Alzheimer’s disease (AD) involves $$β$$ β -amyloid (A $$β$$ β ) accumulation. Early identification of individuals with abnormal $$β$$ β -amyloid levels is crucial, but A $$β$$ β quantification with positron emission tomography (PET) and cerebrospinal fluid (CSF) is invasive and expensive. Methods We propose a machine learning framework using standard non-invasive (MRI, demographics, APOE, neuropsychology) measures to predict future A $$β$$ β -positivity in A $$β$$ β -negative individuals. We separately study A $$β$$ β -positivity defined by PET and CSF. Results Cross-validated AUC for 4-year A $$β$$ β conversion prediction was 0.78 for the CSF-based and 0.68 for the PET-based A $$β$$ β definitions. Although not trained for the clinical status-change prediction, the CSF-based model excelled in predicting future mild cognitive impairment (MCI)/dementia conversion in cognitively normal/MCI individuals (AUCs, respectively, 0.76 and 0.89 with a separate dataset). Conclusion Standard measures have potential in detecting future A $$β$$ β -positivity and assessing conversion risk, even in cognitively normal individuals. The CSF-based definition led to better predictions than the PET-based definition.